Comparing Risk Factors for Prison Victimization Between Foreign-Born and Native-Born Incarcerated People - McNeeley, Susan M. (Crime & delinquency, 2025)
Prior research on violent victimization in prison suggests noncitizens may be less likely to experience violence while incarcerated. In an attempt to better understand this relationship, this study examined whether citizenship status predicts risk among a subsample of foreign-born incarcerated people. In addition, we modeled violent victimization separately for foreign-born and native-born individuals to identify any differences in risk factors between groups. We tested these relationships using a sample of 7,326 individuals incarcerated in Minnesota state prisons. The results of Cox regression models showed foreign-born citizens and foreign-born noncitizens had similar risk for violent prison victimization. We also found that some risk factors for victimization differed across native-born and foreign-born incarcerated people.